2010
DOI: 10.1115/1.4002768
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Laser Induced Structural Modification of Fused Silica—Part II: Spatially Resolved and Decomposed Raman Spectral Analysis

Abstract: Nonlinear absorption of femtosecond laser pulses enables the induction of structural changes in the interior of bulk transparent materials without affecting their surface. In the present study, femtosecond laser pulses were tightly focused within the interior of bulk fused silica specimen. Localized plasma was formed, initiating rearrangement of the random network structure. Cross sections of the induced features were examined via decomposition of spatially resolved Raman spectra and a new method for the quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…To evaluate the amount of various ring structures in the network of silica glass formed by silicon and oxygen atoms, the obtained Raman spectra were fitted by three Lorentzian function series, which correspond to the ½ 1 band (five-and six-membered rings), D 1 band (four-membered ring), and D 2 band (three-membered ring), respectively, as given by: 13) …”
Section: Micro-raman Spectroscopy Of Asymmetric δN Structurementioning
confidence: 99%
“…To evaluate the amount of various ring structures in the network of silica glass formed by silicon and oxygen atoms, the obtained Raman spectra were fitted by three Lorentzian function series, which correspond to the ½ 1 band (five-and six-membered rings), D 1 band (four-membered ring), and D 2 band (three-membered ring), respectively, as given by: 13) …”
Section: Micro-raman Spectroscopy Of Asymmetric δN Structurementioning
confidence: 99%
“…From this figure, it can also be observed that [43]. Figure 10: Volume fraction distribution of (a) five-and sixmembered rings based on the 440 cm-1 peak, (b) fourmembered rings based on the 495 cm-1 peak, and (c) threemembered rings based on the 606 cm-1 peak in Raman spectra of cross section of laser-irradiated region (pulse energy of 30 μJ and federates of 0.04 mm/s) [39].…”
Section: Weld Formation and Geometrymentioning
confidence: 94%
“…Decomposition of the Raman spectra in the region between wavenumbers 300 cm -1 and 630 cm -1 , where three distinctive peaks corresponding to the different ring structures were observed, was performed through a curve fitting process [39]. It is assumed that within the volume of interest four different structures coexist three-, four-, five-and six-membered rings.…”
Section: Changes In Ring Structures and Their Volume Fractions By Rammentioning
confidence: 99%
See 1 more Smart Citation
“…Cross sections of induced features are examined via decomposition of the spatially resolved Raman spectra and quantitative characterization of the structure of amorphous fused silica is developed. This method identifies the volume fraction distribution of ring structures and changes of the distribution with laser process conditions [12]. Fractional wavelet transform (FWT) is a powerful tool to extract largest analytical information from the spectral bands.…”
Section: Introductionmentioning
confidence: 99%